The simulation of paintings with different aesthetic variables Temperature and Harmony - Nedvědová, Marie; Marek, Jaroslav (IEEE (Institute of Electrical and Electronics Engineers), 2017)
The aesthetic characteristics Temperature and Harmony were suggested for measuring of aesthetic impression image composed of simple patterns. These characteristics are influenced by the number of different types of elements contained in the image, and the number of different symmetries in their arrangement. Full details of all steps in these calculations are given in this paper. The primary concern of this reseach is to investigate the two-dimensional domain of characteristics Temperature and Harmony that depends on the number of different elements. With the use of random generation and evolutionary algorithms, thousands of images will be generated.
Generování obrazů s různými hodnotami estetických proměnných teplota a harmonie
Keywords: mathematical aestetics; aesthetic variables Temperature and Harmony; evolutionary algorithms; matematická estetika; estetické charakteristiky teplota a harmonie; evoluční algoritmy